Diseño del fluido de perforación mitigando el daño de formación en la zona de interés del pozo 0224 en el Campo Orito (2016)
The Orito Field, discovered in 1963 in the southwestern part of Colombia belonging to the Caguan - Putumayo basin, is being developed through a well drilling plan to mitigate damage to drilling fluid formation, in order to increase Productivity of wells completed in the Caballos Formation. Pacific Exploration & Production is currently in charge of operating the field through an incremental production contract.